The Non-Adiabatic Stereodynamics Study for the Reaction of $Na(3s)+H_2→NaH (X^1Σ^+)+H$ (Journal of Atomic and Molecular Sciences, 2016)
A theoretical investigation of the non-adiabatic dynamics processes for thereaction $Na(3s) + H_2 → NaH (X¹Σ^+) + H$ has been performed using the method of coherenceswitching with decay of mixing (CSDM). The integral cross sections calculatedby the CSDM method are compared with the results from an adiabatic quasiclassicaltrajectory (QCT) calculation, which uses the same potential energy in the adiabaticrepresentation. The product rotational polarization in non-adiabatic dynamics is presentedand compared with the adiabatic results by means of the joint distributions ofrotational angular momentum vectors in the scattering coordinate. It is found thatthe conical intersection shows significant influence on the integral cross sections of thereaction. The adiabatic effect also reduces the rotational polarization of the productNaH.